2000
DOI: 10.1074/jbc.m002765200
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of a Recombinant Human CCR5-specific Antibody

Abstract: We describe the isolation of a CCR5-specific antibody, ST6, from an antibody phage display library generated from an immune rabbit. ST6 was previously shown to efficiently prevent the surface expression of CCR5 when expressed intracellularly (Steinberger, P., Andris-Widhopf, J., Buhler, B., Torbett, B. E., and Barbas, C. F., III (2000) Proc. Natl. Acad. Sci. U. S. A. 97, 805-810). Because ST6 has therapeutic potential in human immunodeficiency virus, type 1 disease, its humanization was desired to minimize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“…55 The intrabody binding motif partially overlaps with the gp120 binding and fusion motif. [56][57][58][59][60] To further improve cellular efficacy of the intrabody, a KDEL endoplasmic retention signal has been included, which provides entrapment of newly synthesized and recycled CCR5 as well and maintains cellular compartmentalization of the CCR5 intrabody.…”
Section: Ccr5 Intrabody-mediated Protection and Enrichment Of T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…55 The intrabody binding motif partially overlaps with the gp120 binding and fusion motif. [56][57][58][59][60] To further improve cellular efficacy of the intrabody, a KDEL endoplasmic retention signal has been included, which provides entrapment of newly synthesized and recycled CCR5 as well and maintains cellular compartmentalization of the CCR5 intrabody.…”
Section: Ccr5 Intrabody-mediated Protection and Enrichment Of T Cellsmentioning
confidence: 99%
“…81 The humanized CCR5 intrabody, ST6/34, was generated and cloned as described previously. 55 The CAD-R5 CCR5 intrabody vector was constructed from CAD by replacing the BamHI MND promoter fragment with an MND promoter and the intrabody fragment.…”
Section: Generation Of the Cad And Cad-r5 Hiv-1 Sin Vectorsmentioning
confidence: 99%
“…Hybridoma screening (see under "Materials and Methods") resulted in the selection of seven VEGF neutralizing antibodies (375, 435, 509, 511, 534, 567, and 578) that potently blocked binding of VEGF to hVEGFR2, and eight TNF-␣ neutralizing antibodies (1,6,15,19,34,35,42, and 43) that potently inhibited TNF-␣-induced apoptosis in the murine L929 cell line. Sequence analysis of the rabbit monoclonal antibodies showed that 7 germ lines (out of 65 functional VL-gene segments) were represented in the selected binders (Table 1).…”
Section: Selection Of Rabbit Monoclonal Antibodies From Hybridomas-mentioning
confidence: 99%
“…Rabbit mAbs generated by phage display offer additional advantages due to the fact that phenotype and genotype are selected at the same time. Knowledge of the rabbit mAb sequence allows the ready generation of a variety of mAb formats, including scFv, Fab, and IgG, and, importantly, humanization and affinity maturation Steinberger et al, 2000;Rader, 2001). Consequently, rabbit mAbs generated by phage display have become promising reagents for therapeutic applications in humans.…”
Section: Introductionmentioning
confidence: 99%